2008
DOI: 10.1007/s10681-008-9776-4
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of resistance to flower bud thrips (Megalurothrips sjostedti) in cowpea (Vigna unguiculata [L.] Walp.)

Abstract: Cowpea is an important legume in subSaharan Africa where its protein rich grains are consumed. Insect pests constitute a major constraint to cowpea production. Flower bud thrips (FTh) is the first major pest of cowpea at the reproductive stage and if not controlled with insecticides is capable of reducing grain yield significantly. Information on the inheritance of resistance to FTh is required to facilitate breeding of resistant cultivars. The genetics of resistance was studied in crosses of four cowpea lines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 9 publications
5
32
1
Order By: Relevance
“…Similar findings were reported by Omo-Ikerodah et al (2009) in Nigeria under field conditions, while evaluating the resistance of Sanzi, and TVu 1509 to flower thrips. In contrast, Alabi et al (2003) in Nigeria and Abudulai et al (2006) in Ghana, reported that the resistance in some cowpea cultivars under natural infestation was due to flower thrips infestation escape due to early flowering.…”
Section: Pc1 -6096%supporting
confidence: 86%
See 2 more Smart Citations
“…Similar findings were reported by Omo-Ikerodah et al (2009) in Nigeria under field conditions, while evaluating the resistance of Sanzi, and TVu 1509 to flower thrips. In contrast, Alabi et al (2003) in Nigeria and Abudulai et al (2006) in Ghana, reported that the resistance in some cowpea cultivars under natural infestation was due to flower thrips infestation escape due to early flowering.…”
Section: Pc1 -6096%supporting
confidence: 86%
“…is the most well-known Papilionaceae species with an African origin (Omo-Ikerodah et al, 2009). The crop is an important staple food legume and inexpensive source of protein for many resource poor African households.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The critical yield losses caused by these insect groups make them a priority focus in cowpea breeding. In the case of flower thrips, Omo-Ikerodah et al (2008) identified DNA markers associated with QTLs that have effects on resistance to flower bud thrips in a biparental mapping population derived from a cross that had Sanzi, the land race from Ghana, as one of the parents. Many other improved breeding lines with resistance to diseases, drought, Striga, and pests were derived from crosses that involved above listed (Table 7.1) and other germplasm lines.…”
Section: Resistance To Insect Pestsmentioning
confidence: 99%
“…One biparental population consists of 94 RILs developed at the University of California, Riverside, derived from a cross between "California Blackeye 27" (CB27), which has a medium-sized black eye seed coat and purple pod tips, and "IT82E-18," which has a solid brown coat and green pod tips (Muchero et al 2009). The other biparental RIL population was provided by the International Institute for Tropical Agriculture and consists of 121 RILs derived from a cross between "Sanzi," a landrace with a speckled black and purple seed coat and purple pod tips, and "Vita 7," which has a solid tan coat and green pod tips (Omo-Ikerodah et al 2009). The seeds of each of these four parents are shown in Figure 1A.…”
Section: Plant Materialsmentioning
confidence: 99%